Environmental, Social, and Governance (ESG) and Firm Valuation : The Moderating Role of Audit Quality - Vaihekoski, Mika; Yahya, Habeeb (MDPI, 2025)
This paper investigates whether the external audit quality has an impact on the link between ESG performance and firm valuation using a sample of publicly listed Nordic firms. The results from a fixed-effect panel regression show that higher ESG scores lead to higher valuation when a Big Four audit firm is engaged as the external auditor, highlighting the impact of audit quality on the the reliability of the ESG evaluation. The finding highlights the importance of intense external audits in reinforcing investors’ confidence in ESG–firm valuation assessment.